The Role of Local Wisdom Integrated Worksheets in Strengthening Students' Environmental Awareness - Syarkiah Amaliah, Mutahharah Hasyim*, M.A. Martawijaya, Muhammad Taqwin (Physics Education, 2024)
The Role of Local Wisdom Integrated Worksheets in Strengthening Students' Environmental Awareness. The purpose of this study is to determine the ability of students to write ideas by utilizing physics concepts to care for the environment. This research was carried out at SMA Negeri 5 Sidrap and the location of Blacksmith with the research subjects of 3 students in class XI MIPA 1 SMA Negeri 5 Sidrap. The test subjects are students who like to learn physics and are considered less concerned about the environment. Research instruments used by human instruments. The data collection techniques used are observation, written tests, and unstructured interviews. The worksheet was designed by referring to local wisdom in Sidrap with the object